Scandinavia - Time-Life Books (Alexandria, Va. Time-Life Books, 1987)
An introduction to the geography, history, economy, government, and people of Denmark, Norway, Sweden, Iceland, and Finland.
Includes index.
Maps on lining papers.
Bibliography: p. 156-157.
Keywords: Escandinavia; Finlandia; Scandinavia; Scandinavia